Mesenchymal stem cells from human adipose tissue and bone repair: a literature review. Issue 1 (January 2018) - Alonso-Goulart, Vivian; Ferreira, Lorraine Braga; Duarte, Cristiane Angélico; Lima, Isabela Lemos de; Ferreira, Enza Rafaela; Oliveira, Bárbara Candido de; Vargas, Luna Nascimento; Moraes, Dayane Dotto de; Silva, Isaura Beatriz Borges; Faria, Rafael de Oliveira; Souza, Aline Gomes de; Castro-Filice, Leticia de Souza
Abstract: Mesenchymal stem cells (MSCs) emerge as potential tools for treatment of various diseases. Isolation methods and tissue of origin are important factors that determine the amount of obtained cells and their ability to differentiate. MSCs can be isolated from adipose tissue (ADSCs), bone marrow (BMSCs) or umbilical cord (UC-MSCs), and its characterization must follow the criteria required by the International Society for Cellular Therapy. Osteogenic differentiation capacity of ADSCs can still vary according to the culture medium used, as well as by adding factors that can alter signaling pathways and enhance bone differentiation. In addition, nanotechnology has also been used to increase osteoblastic induction and differentiation. ADSCs enhanced the prospect of treatment in different diseases, and in regenerative medicine, these cells can also be associated with different biomaterials. There is a great progress in studies with ADSCs, mainly because it is easy to access, which makes bioengineering techniques for bone tissue feasible.